2017
DOI: 10.1021/acs.jafc.7b01401
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Controlled-Release Avermectin/Castor Oil-Based Polyurethane Nanoemulsions

Abstract: Avermectin (AVM) is a low-toxic and high-active biopesticide, but it can be easily degraded by UV light. In this paper, biodegradable castor oil-based polyurethanes (CO-PU) are synthesized and used as carriers to fabricate a new kind of AVM/CO-PU nanoemulsion through an emulsion solvent evaporation method, and the chemical structure, colloidal property, AVM loading capacity, controlled-release behavior, foliar adhesion, and photostability of the AVM/CO-PU drug delivery systems are investigated. Results show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 46 publications
1
47
0
Order By: Relevance
“…These results indicated the insecticidal activity of GBEE was improved after encapsulated by nanoemulsion. Similarly, many results have been reported that nanoemulsion can enhance the oil solubility and the pesticides bioavailability ascribing to the small droplet size [45,46]. In contrast, similar LC 50 were obtained at 12 h regardless of the droplet size.…”
Section: Insecticidal Activity Of Nanoemulsionsupporting
confidence: 60%
“…These results indicated the insecticidal activity of GBEE was improved after encapsulated by nanoemulsion. Similarly, many results have been reported that nanoemulsion can enhance the oil solubility and the pesticides bioavailability ascribing to the small droplet size [45,46]. In contrast, similar LC 50 were obtained at 12 h regardless of the droplet size.…”
Section: Insecticidal Activity Of Nanoemulsionsupporting
confidence: 60%
“…On the other hand, the use of pesticides identified with toxicity and carcinogenicity will lead to chemical persistence in agricultural products and environmental problems, though it can protect the agricultural cultivation from insects and ensure mass production of food to feed the growing population [18,19]. For example, acetamiprid [(E)-N1-[(6-chloro-3-pyridyl) methyl]-N2-cyano-N1-methylacetamidine, Fig.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Aer 0.5 h of neutralization, the CO-PU prepolymer was prepared. 32 Subsequently, according to the designed formula in Table 1, certain amount of the pre-dissolved LC solution in acetone and the CO-PU prepolymer was rst mixed, and a predetermined amount of water was then charged into the system, and in situ soap-free phase inversion emulsication was conducted at 1100 rpm for 40 min. Finally, the LC/CO-PU nanoemulsions were obtained by removing acetone with vacuum rotary evaporation.…”
Section: Preparation Of Lc/co-pu Nanoemulsionsmentioning
confidence: 99%
“…A facile and economic method was used to fabricate LC/CO-PU nanoemulsions, in which the CO-PU prepolymer with hydrophilic carboxyl groups was rst synthesized by step-growth addition polymerization (Fig. 1), 32 and then the homogeneous acetone solution of the CO-PU prepolymer and LC was dispersed in water through vigorous stirring via self-emulsication process as shown in Fig. 2.…”
Section: Preparation Of Lc/co-pu Nanoemulsionsmentioning
confidence: 99%